Synthesis and characterization of 1,2,4-triazole containing hydrazide-hydrazones derived from (S)-Naproxen as anticancer agents - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (MARMARA UNIV, 2018)
A novel series of new naproxen derivatives (S)-ethyl{[4-(4-fluorophenyl)-5-[(1-(6-methoxynaphtalen-2-yl)ethyl)]-4H-1,2,4-triazole-3-yl]sulphanyl}acetate (5), (S)-2-({5-[1-(6-methoxynaphtalen-1-yl)ethyl]-4-fluorophenyl-4H-1,2,4-triazole-3-yl}sulphanyl)acetohydrazide (6), 2-{[5-[1-(6-methoxynaphtalen-2-yl)ethyl]-4-(4-fluorophenyl)-4H-1,2,4-triazole-3-yl]sulphanyl}-N'-[(substituted)methylidene]acetohydrazides (7a-m) were synthesized, in this study. The structures of compounds 5, 6 and 7a-m were defined by spectral (H-1-NMR, C-13-NMR, HR-MS and FT-IR) methods and their purity was proven by elemental analysis, thin layer chromatography and high pressure liquid chromatography. These compounds were evaluated for in vitro anticancer activity by using MTS method against PC-3 and DU-143 (androgen-independent human prostate cancer cell lines) and LNCaP (androgen-sensitive human prostate adenocarcinoma) prostate cancer cell lines. Cisplatin was used as the positive sensitivity reference standard. Compounds (7a-m) exhibited anticancer activity with IC50 values of 87.2-400 mu M against prostate cancer cell lines.
Keywords: Anticancer activity; MTS method; (S)-Naproxen; hydrazide-hydrazones; MICROWAVE-ASSISTED SYNTHESIS; DIFLUNISAL HYDRAZIDE; ANTIPROLIFERATIVE ACTIVITY; BIOLOGICAL-ACTIVITIES; ANTI-HCV; DERIVATIVES; APOPTOSIS; NAPROXEN; ETODOLAC; ANALOGS